Strategi Diplomasi Kemanusiaan Pemerintah Indonesia Dalam Kasus Krisis Kemanusiaan Yang Dialami Etnis Rohingya Di Myanmar Tahun 2017 - Fernando Ersento Maraden Sitorus, Ardli Johan Kusuma , (Mandala: Jurnal Ilmu Hubungan Internasional, 2019)
This research wants to look at the humanitarian diplomacy strategy by the Indonesian government to provide humanitarian assistance to the Rohingya ethnic groups (especially those still in Myanmar in 2017). Myanmar's military and also the majority of people in Rakhine who are Buddhists have committed acts of violence and seized the human rights of the Rohingya ethnic group which is an ethnic minority in Rakhine who are Muslim. The issue attracted the attention of the international community, including Indonesia. This study uses a qualitative method, with a descriptive analytic approach, where data are collected by literature study. The findings of this study are: the Indonesian government has used several humanitarian diplomacy strategies, including: conducting a diplomatic approach between the Indonesian government and the Myanmar government (with due regard to the ASEAN Way), collaborating with the United Nations (offering formula 4+1 as a form of implementation of the recommendations from Advisory Commission Report for Rakhine), involved civilians to channel aid to the Rohingya ethnic group in Myanmar (forming AKIM consisting of 11 humanitarian agencies). The strategy succeeded in breaking through the blockade carried out by the Myanmar government as an effort to block humanitarian assistance provided by the international community.